The problems facing the plastic industries in the city of Baghdad, the pollutants resulting from them, and future policies and strategies using (SWOT) analysis for 2021 - Mohamed, Joan; AlUsami, Zainab (Al-Adab Journal, 2024)
The plastic industry is one of the basic and vital chemical industries because of its important role in the national economy and the enhancement of national income and its importance in attracting numbers of manpower, in addition to its importance to other industries due to the existence of industrial links between them.    The importance of plastic industries in the study area, Baghdad, lies in the availability of most of the natural and human ingredients in it, as the city of Baghdad constitutes an important geographical location with many foundations that pave the way for the establishment and development of the plastic industry.    Plastic industries, like other industries, suffer from many problems, so they will be studied, and appropriate solutions will be developed to eliminate these problems or reduce them, in addition to that, knowing the pollutants resulting from the plastic industries and their impact on the city of Baghdad, as well as using SWOT analysis to know the strengths, weaknesses, opportunities and threats points for these industry for its future development.